Introductory readings in education - Mayer, Frederick (Belmont, California : Dickenson Publishing Company, Inc., 1960)
This book of readings is designed to develop perspective on the part of the reader and to give him enthusiasm for the possibilities of the American school system. Without a fervent faith in education as a way of life, we cannot overcome the cultural lags of our time.
1. On religious education / Jonathan Edwards -- 2. The education of youth in Pennsylvania / Benjamin Franklin -- 3. Notes on Virginia ; Letter to John Adams ; Letter to George Ticknor ; Letter to Joseph C. Cabell ; Letter to William B. Giles / Thomas Jefferson -- 4. On public education / DeWitt Clinton -- 5. A plan for improving female education / Emma Willard -- 6. Town lyceums / Josiah Holbrook -- 7.Infant instruction / Amos Bronson Alcott -- 8. Education of Americans in Europe / Noah Webster -- 9. Plea for free schools in Pennsylvania / Thaddeus Stevens -- 10. Mount Holyoke Seminary / Mary Lyon -- 11. The American scholar / Ralph Waldo Emerson -- 12. Walden [excerpt] / Henry David Thoreau -- 13. Reply to remarks of Boston schoolmasters ; Report on education / Horace Mann -- 14. The kindergartner / Elizabeth Peabody -- 15. Talks on pedagogics / Francis Wayland Parker -- 16. Early days at Tuskegee / Booker T. Washington -- 17. The training of teachers / Stanley Hall -- 18. The psychology of infancy / W.T. Harris -- 19. What is a liberal education? / Charles William Eliot -- 20. The meaning of education / Nicholas Murray Butler -- 21. Talks on psychology / William James -- 22. My pedagogic creed / John Dewey -- 23. On education / Robert Hutchins -- 24. Strengthening the free world / John Fitzgerald Kennedy.
Includes bibliographical references.
Keywords: EDUCATION